GAAS-BASED Virtual Pets for Engaging Generation Z in Borneo Wildlife Conservation: a Preliminary Research: A Preliminary Research - Pahlevy, Trianata; Grahita, Banung (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
This preliminary research investigates the potential of a Game as a Service (GaaS)-based virtual pet game to enhance Generation Z's engagement in wildlife conservation efforts for endangered species in Borneo. Employing a Design Research approach and the Double Diamond Framework (Discover and Define phases), the study analyzes data from semi-structured interviews with ten Generation Z respondents to examine in-app purchase motivations (IAP), gameplay preferences, and design considerations. The results identify five key game pillars: (1) empathy-building through character personalization and anthropomorphism; (2) a progression system linking in-game achievements to real-world conservation actions; (3) layered monetization strategies leveraging fear of missing out (FOMO) and aesthetic appeals; (4) social mechanics integrating collaborative and competitive elements; and (5) adaptive educational narratives tailored to player types. These findings delineate an emotionally engaging game design framework that responds to the discourse on creative conservation funding while enabling potential partnerships with conservation organizations. This study contributes to virtual pet design exploration and offers an adaptable framework for addressing wildlife conservation challenges in other regions.